(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the publication is presented analytical studies about an analyze of of boring heads cutting part accuracy for combined tools for machining holes by cutting and burnishing. It was found that the accuracy of the static size of the tool when using triangular and square inserts is determined by tolerances of inserts sides. When using round inserts, static radius error depends only on insert radius error.The conclusions drawn show that by determining appropriate tolerances for elements of fixtures, the specified accuracy of the processed parts is ensured.